Features of studying a communicative discourse within a competence approach - Elena V. Maksimyuk (Вестник Самарского государственного технического университета. Серия: Психолого-педагогические науки)
The paper is devoted to the need to include tasks aimed at a comprehensive analysis of the extra-linguistic factors of the communication situation in the teaching aids. Understanding the external context will allow us to create the conditions for effective decision making based on the use of sociocultural experience. The author demonstrates that the introduction of contextual analysis with an emphasis on socio-psychological content will make the process of teaching foreign languages practical-oriented and will contribute to the formation of competencies necessary for foreign language communication. Particular emphasis is placed on the genre filling of speech. Since genres of communication are a verbal reflection of the types of social interaction of people. The speech genre is the norm necessary for the realization of a communicative goal within the framework of the chosen message format. The specificity of communication is due to the unique combination of socio-psychological elements that determine the nature of the relationship within it. The paper describes and analyzes the thematic and genre content, taking into account the psycho-emotional characteristics of speech in the framework of professional communication between the boss (Dr. Cuddy) and his subordinate (Dr. House). The study used methods: contextual, genre, cognitive-semantic and comparative analysis. The author demonstrates that contextual analysis is an effective way of forming and implementing value-semantic, cultural, educational, cognitive and informational competence. Since knowledge and understanding of the role of extra-linguistic factors in the communication process largely determine the success of communication and the degree of effectiveness of using various language tools and speech tactics and strategies. The inclusion in the educational and methodological complexes for teaching a foreign language of tasks aimed at analyzing an external context that is close to real will contribute to the implementation of new approaches to teaching foreign languages in higher education, the further implementation of new federal state standards, and contribute to the achievement of the main goal of teaching foreign languages - the formation of a secondary linguistic personality, ready for foreign language communication in a multicultural world in a pandemic circumstances.